Job Dissatisfaction Mediated the Associations Between Work Stress and Mental Health Problems - Qiu, Dan; Li, Ruiqi; Li, Yilu; He, Jun; Ouyang, Feiyun; Luo, Dan; Xiao, Shuiyuan (Frontiers in Psychiatry, 2021)
Abstract Objective: This study aimed at explore the relationships and the underlying mechanisms between work stress and mental health problems, and potential mediation effects through job dissatisfaction in a working population. Methods: A large population-based study among workers in China was conducted. The self-reported scales of assessing job dissatisfaction and work stress were included in the questionnaire. Generalized Anxiety Disorder-2 and Patient Health Questionnaire-2 were used for assessment of mental health. Univariate logistic regression was conducted to test the associations between work stress and mental health. Path analysis was conducted to test the proposed mediation model. Results: Of the 6190 included employees, 27.72% reported that they perceived work stress, 14.84% of them reported that they were not satisfied with their work, 5.01% of the employees reported depressive symptoms and 3.75% of the employees reported anxiety symptoms. The results of univariate logistic regression showed that employees who perceived work stress were more likely to report anxiety symptoms (AOR = 2.78; 95% CI: 2.03–3.79) or depressive symptoms (AOR = 1.61; 95% CI: 1.22–2.12). The path analysis showed that work stress was positively associated with job dissatisfaction. Job dissatisfaction mediated the relationship between work stress and mental health problems among Chinese working adults. Conclusion: This study suggests the importance of psychosocial work environment for mental health among Chinese working adults. Work dissatisfaction are stressors that may induce negative consequences on mental health among Chinese workers. Interventions to help workers with stress management may be beneficial for their mental health.